(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
This article proposed an analysis of an artistic research workshop, conducted as part of the project Historiografías en movimiento (PICTO-UNA-00007). It reflected on the category of reenactment through work with the ballet Orpheus and Eurydice (1960), by Argentine choreographer Roberto Giachero. A corporeal approach was taken to a series of materials understood as the traces of an incomplete archive. This article proposed the category of "doing again" to account for the historiographic methodology explored in the workshop, through which historical linearity was questioned and a figure omitted from the history of Argentine dance was made visible.